PENGARUH GAYA HIDUP TERHADAP MINAT BELI PRODUK KAYU TREE-X - Yashinta Armadita Hadi; Damelina Basauli Tambunan; Yoseva Maria Pujirahayu Sumaji (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
Covid-19 pandemic causes great impact on all aspects. Event a lot of companies hold to do marketing activity for a while until the condition starts to be normal and under controlled. Each individual reaction on crisis situation during pandemic like recently is different. In addition, during the pandemic, it also causes change of consumer behavior. Survey that had been done by BPS in 2020 showed that there was income change either UMK or UMB. There was income change of course got decreased of 82.29% for UMB and as many as 84.20% for UMK. This income change was caused by its decrease of economic condition due to Covid 19. Its weakening of community purchase intention played great role in income decrease that was experienced by UMK and UMB. This research is done to test the lifestyle factor of risk takers on handicraft product purchase intention, the lifestyle factor of experiencers on handicraft product purchase intention and the lifestyle factor of traditionalists on handicraft product purchase intention. This research uses quantitative method. The population of the research is men and women age of 18 to 29 years old in which its number is certainly unknown. The sampling technique in this research is non-probability sampling with 96 samples. The tool that is used in this research is SPSS 22. This research uses multiple linear regression analysis. The result of this research is the lifestyle of risk takers and the lifestyle of traditionalists significant effect on handicraft product purchase intention. Keywords: Lifestyle of risk takers, Lifestyle of experiencers, Lifestyle of traditionalists, purchase intention